Pengaruh Seni Tari Terhadap Perkembangan Kemampuan Fisik dan Motorikanak di Ra Al Bayyan Jamanis - Uminah Uminah; Rosita Wulandari; Siti Hazar Agisah; Iip Apipah (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2023)
The motoric development is physical development when a child is born. Children can control gross movements quickly when they are four or five years old. Development and growth in children is an aspect that most needs to be known by parents and teachers, one of which is the physical and motor development of children. Dance is a form of artistic expression involving coordinated, rhythmic and expressive body movements. The art of dance is believed to be able to stimulate the physical and motor skills of children. This study aims to determine the effect of dance on the physical-motor development of early childhood at RA Al Bayyan Jamanis. This research method uses a qualitative approach. The results showed that the art of dance can stimulate the physical motor in children and stimulate the development ofthe child's brain. This can be seen when the Child is able to coordinate his body movements according to the rhythm that is played, the Child tries to imitate the movements demonstrated by the teacher. Our findings highlight that in addition to being able to train physical motor development, dance can also train concentration in early childhood.